Synthesis of novel 6-substituted thymine ribonucleosides and their 3′-fluorinated analogues. Issue 41 (13th October 2016) - Bozhok, Tatyana S.; Sivets, Grigorii G.; Baranovsky, Alexander V.; Kalinichenko, Elena N.
Abstract: Nine novel 6-fluorothymine nucleoside analogues of both N(1)-α/β and N(3)-β-ribo series were prepared by the Vorbrüggen method starting from persilylated 6-fluorothymine and 1-O-acetyl-2, 3, 5-tri-O-benzoyl-β-d -ribofuranose, 1-O-acetyl-2, 5-di-O-benzoyl-3-deoxy-3-fluoro-α, β-d -ribofuranose or 1, 2, 3, 5-tetra-O-benzoyl-β-d -ribofuranose and its α-anomer. Protected N(3)-β-d -ribofuranosides were prepared as sole products in high yields at room temperature. A mixture of benzoylated N(1)-β- and α-anomeric ribonucleosides was obtained at lower temperatures. Yields of β-anomers and stereoselectivities (β:α=2.2/4.5:1) of the condensation reactions depended on reaction conditions and the structure of the glycosylating agent. Debenzoylation of 6-fluorothymine N(1)- or N(3)-β-d -ribofuranosides and their 3′-fluorodeoxy analogues by LiOH monohydrate in MeCN/H2 O resulted in the corresponding fluorinated nucleosides in good yields, whereas the deprotection of N(1)-α-ribofuranosides under the same conditions unexpectedly yielded 6, 2′-O-α-d -anhydronucleosides. 6-Substituted (OMe, NH2 ) thymine β-ribonucleosides were prepared by the treatment of protected N(1)-β-d -ribosides with nucleophilic agents. Graphical abstract: